Influence of solid-state interfacial reactions on the tensile strength of Cu/electroless Ni–P/Sn–3.5Ag solder joint - Kumar, Aditya (2013)
Tensile strength and fracture behavior of Cu/electroless Ni–P/Sn–3.5Ag (wt.% Ag) solder joint were investigated under high-temperature solid-state aging. The aging results showed that the Ni3Sn4 intermetallic phase grows at the electroless Ni–P/Sn–3.5Ag interface, along with the transformation of the underlying electroless Ni–P layer into Ni3P compound. However, after complete consumption of the electroless Ni–P layer, a ternary Ni–Sn–P compound also starts to grow between Ni3Sn4 and Ni3P layers in conjunction with the depletion of Cu from the Cu surface. It was found that while both the growth of Ni3Sn4 and depletion of Cu deteriorate the solder joint strength, the strength is deteriorated more with the latter. The growth of Ni3Sn4 and depletion of Cu were found to influence the failure mode and fracture surfaces of the solder joint, also. The failure mode changed from ductile to brittle and the fracture surfaces shifted from inside the bulk solder to the Ni3Sn4/Sn–3.5Ag interface due to the growth of Ni3Sn4. The failure mode became very brittle and the fracture surfaces shifted to the interface between Cu surface and Ni3P or Ni–Sn–P layer due to the depletion of Cu.